Cooperative Economies and Collective Growth: A Hyperlocal Framework for Sustainable Economic Exchange - Narayana, Sreedhar Hari (Journal of Global Economy, Business and Finance, 2025)
The proposed cooperative economy is an ethical community-driven exchange system that relies on collective action to promote societal values while accounting for resource constraints. Unlike the modern economic system which is predominantly driven by opportunistic behaviour, the cooperative economy moves away from a materialistic orientation and follows a more balanced perspective that leverages prosocial behaviour. Cooperative economies have gained attention as an alternative approach to traditional economic systems, emphasizing collective growth, localism, and sustainability. We explore the concept of a hyperlocal and sustainable cooperative economy, which by reducing dependence on global supply chains, aims to foster economic exchange within communities while promoting social and environmental well-being. Sustainability has been a core principle of the model, incorporating ecological practices and resource conservation. Renewable energy, waste reduction, and responsible consumption are emphasized, minimizing environmental impact and preserving natural resources. In this paper we also explore the organizational structure of Co-Operative Economies, how they’ve grown throughout the years, the economic impact created by them as well the threats being faced, and what the government can and is doing to remedy such threats.